Strategi Kepemimpinan Kepala Sekolah pada Program Inovasi Peminatan Tahfidz di SMP Muhammadiyah Pekajangan - Dwike Mawar Dhani; Dartim Dartim (Kamaya: Jurnal Ilmu Agama, 2026)
This reseach aims to analyze the principal’s leadership strategies in developing an innovative tahfidz specialization program at SMP Muhammadiyah Pekajangan and to identify the supporting and inhibiting factors in its implementation. A qualitative descriptive approach was employed, with data collected through in-depth interviews, direct observations, and document analysis. The data were analyzed using thematic analysis techniques. The findings reveal that the principal applies a transformational leadership model characterized by a clear and future-oriented vision, encouragement of innovation, and active involvement of teachers and educational staff in program development. This leadership strategy contributes significantly to the sustainability and quality improvement of the tahfidz specialization program. Supporting factors include transformational leadership model, competent tahfidz teachers, adequate facilities, and parental support, while limited instructional time and variations in students’ Qur’anic proficiency remain key challenges. This study contributes theoretically to the discourse on principal leadership in Islamic educational institutions, particularly in strengthening transformational leadership through innovative flagship programs.